Diseño de una metodología de gestión de inventarios para la integración y colaboración en la cadena de suministro del sector madera y muebles de Barranquilla (2014)
The Integration and collaboration in supply chains have been a topic very discussed in the last decades and have brought many benefits such as the reduction of the bullwhip effect, costs saving in logistics operation, among others. The Wood and Furniture Industry of Barranquilla presents weaknesses in inventory management because they have not adopted the best practices to manage the inventories of way collaborative and integrated between the different members in the supply chain. The aim of this research is to design a methodology of inventory management that seeks to improve the current levels of integration and collaboration in the supply chain of the wood and furniture sector in Barranquilla, establishing recruitment policies and integration and collaboration schemes. To achieve this aim, we designed a poll to characterize the sector being obtained levels of internal integration (medium), external integration (low) and collaboration (low). Similarly, the characterization of the sector and a review of the state of the art allowed doing a gap analysis against the best practices to global level and then proposing a methodology for inventory management that allows close those gaps.